Implementasi Konsep Asthabrata sebagai Landasan Hidup Generasi Z - Untoro, Haryo; Mustofa, Daffa Pharaja; Ulumudin, Miktahul (Arnawa, 2025)
Generation Z is often referred to as the "strawberry generation," implying a generation with a weak mentality in the eyes of previous generations. However, like other generations, Generation Z also exhibits characteristics that are both beneficial and challenging. As the future inheritors of civilization, efforts are needed to ensure Generation Z does not truly become the "strawberry generation." One step is to explore the unique leadership values of the Nusantara region, specifically the Asthabrata principles from Yasadipura I's Serat Rama. The objective of this study is to explain the implementation of Asthabrata as a foundation for Generation Z. The research method employed is a descriptive qualitative approach. The data analysis method employed is the Miles & Huberman data analysis method, which consists of four sequential stages: data collection, data reduction, data presentation, and conclusion. In conducting the analysis, the theoretical framework employed is Bronislaw Malinowski's functionalism, combined with Abrams' pragmatic approach. The results obtained indicate that Asthabrata leadership can be implemented in addressing the characteristics of Generation Z. As a foundation for life, Asthabrata leadership can serve as a perspective for Generation Z in selecting and choosing their path toward a better future. === Generasi Z sering dipandang sebagai ‘generasi stroberi’ yang bermakna generasi yang bermental lemah oleh generasi sebelumnya. Akan tetapi, sama seperti generasi lainnya, generasi Z juga memiliki karakteristik yang dinilai baik dan buruk. Sebagai penerus peradaban ke depan, dibutuhkan upaya agar generasi Z tidak benar-benar menjadi generasi stroberi. Salah satu langkahnya adalah menggali nilai-nilai kepemimpinan khas Nusantara, dalam hal ini Asthabrata dalam Serat Rama karya Yasadipura I. Tujuan dari penelitian ini adalah menjelaskan implementasi Asthabrata sebagai landasan generasi Z. Metode penelitian bersifat deskriptif kualitatif. Adapun analisis data menggunakan metode analisis data Miles & Huberman yang memiliki empat tahap secara berurutan, yaitu tahap pengumpulan data, reduksi, penyajian, dan penarikan kesimpulan. Dalam melaksanakan analisis, teori yang digunakan adalah fungsionalisme Bronislaw Malinowski dengan pendekatan pragmatic Abrams. Hasil yang didapatkan, bahwa kepemimpinan Asthabrata dapat diimplementasikan dalam menghadapi karakteristik generasi Z. Sebagai landasan berkehidupan, kepemimpinan Asthabrata dapat menjadi cara pandang bagi generasi Z dalam memilah dan memilih langkahnya menuju masa depan lebih baik.